Social participation in health to Camaragibe city’s users - Frazão, Iracema da Silva (Online Brazilian Journal of Nursing, 2005)
The present study was realized with the objective to evaluate, under the perception of the user, the importance of the social participation to control and improve the health services in the county of Camaragibe, state of Pernambuco. Thus, a questionnaire of open and closed ended questions was prepared. The survey involved 789 users that were inquired about the utilization of the local health services in the last six month that preceded the inquiry. It was verified that the mechanisms of participation, as well as the correlated legislation are not well known nor used by the users. Nevertheless, the percentages of those who utilize these mechanisms of social participation increase according to their educational level. It has been noted that educated individuals who are involved in community associations, have a tendency to use those services in a more effective manner. The users of private health services showed a higher percentage of satisfaction compared with those who depend on the public services. Nevertheless, the level of contentment of the public service users showed that it was significantly increased, not reflecting, however, a high pattern of quality, the reason being, it is justified by the low expectation of those who depend on public services. The identification of barriers and opportunities of the user’s participation to control the quality of health services has to be faced with an ethical compromise of the administration members and one essential element exercised by the upstanding law abiding collective community.